Control de motores a pasos por medio de control numérico aplicado a una máquina de corte por plasma. - Acurio Salguero, Diego Fernando (2022)
The present project is defined according to different parameters focused on the control of stepper motors making use of a very useful tool, this being the computerized numerical control which through software vectorizes images passing them to a G-type language so that communicates with the control software such as MACH 3 in order to apply it to a plasma cutting process, recreating in similarity the design with the cut made in the material to be worked on, this material being metallic, hand in hand it is evident the construction of a structure itself that serves as the basis for the movement transmission system of the CNC machine, it is important to know that computerized numerical control is currently in force within the industry since it helps to optimize different processes in which is applied, taking into account the personalized requirements that are desired for this reason in the course of the document nto the most relevant aspects in its design, construction and control of the CNC equipment are disclosed.